12y=11(y+19)

Simple and best practice solution for 12y=11(y+19) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12y=11(y+19) equation:


Simplifying
12y = 11(y + 19)

Reorder the terms:
12y = 11(19 + y)
12y = (19 * 11 + y * 11)
12y = (209 + 11y)

Solving
12y = 209 + 11y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-11y' to each side of the equation.
12y + -11y = 209 + 11y + -11y

Combine like terms: 12y + -11y = 1y
1y = 209 + 11y + -11y

Combine like terms: 11y + -11y = 0
1y = 209 + 0
1y = 209

Divide each side by '1'.
y = 209

Simplifying
y = 209

See similar equations:

| N-2=5+2n | | -2.06d+2.7=-8.6 | | 8(6-9)=9(2(6)-12)-4(6) | | 7+6-3(1/2x6) | | 4/5=-4/7*g | | -3/3=15 | | 4(-x+2)=-8(-2x-4)+16 | | -(3p-2n-t)= | | -2/7n=-28 | | 5(3x-11)=4(3x-2) | | 14+2x=2+1.05x | | 20x+15=5x+90 | | -5-9=4x+7-3x | | (2a+6b)-(14a-11b)= | | 4=(5y/10)-3 | | 5+4r=-15+8r | | 5(6v-5)=215 | | 2x+10=65-x | | 20x-19=4x+141 | | 3(y+12)=2x | | 16x-13=5x-145 | | 26=1.6Y | | (m+3n)-(5m+7n)= | | 11x-5=5x-107 | | 35+4b=24b-5 | | -88=2(4-6v) | | 2[3y-1]+3[y-4]=13 | | 3(y+12)=2xfory | | 2/3y-26=9 | | 6c-2-3c=16 | | -7/10e=140 | | 2r^2+7r=4 |

Equations solver categories